2017
DOI: 10.1111/flan.12250
|View full text |Cite
|
Sign up to set email alerts
|

Effective Foreign Language Teaching: Broadening the Concept of Content Knowledge

Abstract: Studies investigating teacher candidate performance on traditional assessments of content knowledge place emphasis on just one of many skills needed to be an effective foreign language teacher; they also fail to explain why many teacher candidates with advanced oral proficiency struggle in the classroom and why some with less advanced language skills perform well. Using both quantitative data from Oral Proficiency Interviews, the Praxis Subject Assessment, and the edTPA scores for 21 native‐ and nonnative‐spea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 22 publications
1
31
0
1
Order By: Relevance
“…Recent research has moved beyond reporting whole group performance to investigate the underperformance of specific subgroups of teacher candidates, suggesting possible bias in the assessment. Kissau and Algozzine () found that, of the 21 world language teacher candidates in their study, non‐native speakers of English performed significantly more poorly than their native‐speaking peers for task 3 (2.43 vs. 3.38), on the average rubric score (2.77 vs. 3.36), and on the total rubric score (34.4 vs. 43.82). Russell and Davidson Devall () also reported that non‐native speakers of English struggled in comparison with their native‐speaking counterparts.…”
Section: Review Of Related Literaturementioning
confidence: 97%
See 2 more Smart Citations
“…Recent research has moved beyond reporting whole group performance to investigate the underperformance of specific subgroups of teacher candidates, suggesting possible bias in the assessment. Kissau and Algozzine () found that, of the 21 world language teacher candidates in their study, non‐native speakers of English performed significantly more poorly than their native‐speaking peers for task 3 (2.43 vs. 3.38), on the average rubric score (2.77 vs. 3.36), and on the total rubric score (34.4 vs. 43.82). Russell and Davidson Devall () also reported that non‐native speakers of English struggled in comparison with their native‐speaking counterparts.…”
Section: Review Of Related Literaturementioning
confidence: 97%
“…Initial studies focused on candidate results in early‐adopting programs and highlighted areas where many candidates needed improvement (Burns, Henry, & Lindauer, ; Denton, ; Hildebrandt & Swanson, ). Researchers then began investigating the performance of specific groups of teacher candidates, specifically non‐native speakers of English (Kissau & Algozzine, ; Russell & Davidson Devall, ; Troyan & Kaplan, ), suggesting possible bias in the assessment. As it became increasingly clear that edTPA was a challenging assessment for many teacher candidates, some recent studies have proposed strategies to better support candidates and to improve their performance (Behney, ; Hildebrandt & Swanson, ; Ledwell & Oyler, ; Swanson & Hildebrandt, ).…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…While the WL edTPA remains under researched (Behney 2016;Hildebrandt and Swanson 2016;Kissau and Algozzine 2017;Russell and Davidson Devall 2016;Troyan and Kaplan 2015), this research expands the literature base by examining teacher educators' analyses of edTPA portfolios.…”
Section: Discussionmentioning
confidence: 92%
“…edTPA's subject specificity, widespread usage, high-stakes nature, and focus on learning objectives prompt the present investigation. Given its widespread usage across the country, the World Language (WL) edTPA remains understudied despite recent investigations of the topic (e.g., Behney 2016;Hildebrandt and Swanson 2016;Kissau and Algozzine 2017;Russell and Davidson Devall 2016;Troyan and Kaplan 2015).…”
Section: Introductionmentioning
confidence: 99%